TAX COMPLIANCE AND TAX MORALE: STUDENT’S PERCEPTIONS AS THE FUTURE GENERATION OF TAXPAYERS - Nyoman Yudha Astriayu Widyari; Putu Ayu Diah Widari Putri; Ida Ayu Komang Tiara Pratistha Sari (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2026)
This research aims to obtain empirical evidence regarding the influence of religiosity, trust in the government, perceptions of other taxpayers, national pride, and deterrence factors on tax morale, as well as the direct influence of tax morale on tax compliance. The number of samples used was 115 samples selected using simple random sampling. Data collection was carried out by distributing questionnaires. The data analysis technique in this research uses the SEM-PLS method. Based on the six hypotheses formulated, 3 of them were accepted (H1, H4, H6) and the remaining 3 were rejected (H2, H3, H5). The research results show that religiosity and national pride have a positive effect on tax morale. Furthermore, the test results also show that tax morale has a positive effect on tax compliance. On the other hand, trust in the government and perceptions of other taxpayers have no effect on tax morale. Deterrence factors are said to have a positive effect on tax morale, where this result is not in line with the negative direction hypothesis formulated.